Application of Physiotherapy to Occupational Health and Ergonomics Issues in Stone-Breaker Employees - Wicaksono, Utomo; Prayogo, Dadan; Sadu, Bernadus (Sean Institute, 2022)
It is not a violation of the code of ethics for physiotherapists who wish to work in the field of occupational health and ergonomics, as the field of ergonomics requires knowledge of anatomy, anthropometry, physiology, and biomechanics, all of which are required knowledge for graduates of physiotherapy study programs. Under these circumstances, it can be said that physiotherapy is prepared and linear to work in the field of occupational health and ergonomics. This study aims to apply physiotherapy-based interventions to occupational health and ergonomics issues in stone crushers. This investigation is an experimental study employing the same subject design (treatment by subject design), which is comprised of Periods I and II. There were fourteen respondents to the study. On the dorsalis pedis artery, the 10-pulse method is utilized to calculate the workload. Hand and arm musculoskeletal complaints were measured using a 100mm visual analog scale. Wrist splints, short breaks of 5 minutes every 55 minutes of work, and stretching every 2 hours of work had no effect on reducing workers' pain complaints, but reduced their workload by 11,29 % significantly. There is a need for more specific research to determine whether workers suffer from more serious health issues or chronic diseases.